Detection of elevated levels of tumour-associated microRNAs in serum of patients with diffuse large B-cell lymphoma. - Lawrie, C; Gal, S; Dunlop, H; Pushkaran, B; Liggins, A; Pulford, K; Banham, A; Pezzella, F; Boultwood, J; Wainscoat, J; Hatton, C; Harris, A (2008)
Circulating nucleic acids have been shown to have potential as non-invasive diagnostic markers in cancer. We therefore investigated whether microRNAs also have diagnostic utility by comparing levels of tumour-associated MIRN155 (miR-155), MIRN210 (miR-210) and MIRN21 (miR-21) in serum from diffuse large B-cell lymphoma (DLBCL) patients (n = 60) with healthy controls (n = 43). Levels were higher in patient than control sera (P = 0.009, 0.02 and 0.04 respectively). Moreover, high MIRN21 expression was associated with relapse-free survival (P = 0.05). This is the first description of circulating microRNAs and suggests that microRNAs have potential as non-invasive diagnostic markers for DLBCL and possibly other cancers.